2014
DOI: 10.4236/ojapps.2014.414053
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Control Algorithms for Autonomous Quadrotors

Abstract: The quadrotor unmanned aerial vehicle is a great platform for control systems research as its nonlinear nature and under-actuated configuration make it ideal to synthesize and analyze control algorithms. After a brief explanation of the system, several algorithms have been analyzed including their advantages and disadvantages: PID, Linear Quadratic Regulator (LQR), Sliding mode, Backstepping, Feedback linearization, Adaptive, Robust, Optimal, L1, H∞, Fuzzy logic and Artificial neutral networks. The conclusion … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(66 citation statements)
references
References 26 publications
0
63
0
3
Order By: Relevance
“…where Γ σ = [k 11 k 12 k 21 k 22 k 31 k 32 µ 1 µ 2 µ 3 α 1 α 2 α 3 ], σ = {x, y, z, φ, θ, ψ} while for the LPID controller (25) where Γ σ = [Kp Kd Ki], σ = {x, y, z, φ, θ, ψ} The ITAE and USQR are defined in Table 3. The weighting variables must satisfy w 1i + w 2i = 1, They are defined as the relative emphasis of one objective as compared to the other.…”
Section: Step Reference Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…where Γ σ = [k 11 k 12 k 21 k 22 k 31 k 32 µ 1 µ 2 µ 3 α 1 α 2 α 3 ], σ = {x, y, z, φ, θ, ψ} while for the LPID controller (25) where Γ σ = [Kp Kd Ki], σ = {x, y, z, φ, θ, ψ} The ITAE and USQR are defined in Table 3. The weighting variables must satisfy w 1i + w 2i = 1, They are defined as the relative emphasis of one objective as compared to the other.…”
Section: Step Reference Trackingmentioning
confidence: 99%
“…Other used controllers like: NLPID control [17] and [18], LQR [19], geometric control [20], nonlinear model predictive control [21], L1 control [22], fuzzy control [23,24]. A further studies for control algorithms with quadrotor systems can be found in [25].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal control theory is widely applied to design both LQR and LQG controllers for the UAV applications. In [11,12,14,17,19], the dynamic controller synthesis based on LQtechniques is presented. The design criteria applied in this article leans on [15,16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the utility and growing popularity of unmanned aerial vehicles (UAV), especially in military field [1], various methods of control have been developed [2][3][4][5]. One important aspect of controlling these platforms is waypoint following, or trajectory tracking.…”
Section: Introductionmentioning
confidence: 99%